Current trials in erythropoietic protoporphyria: are placebo controls ethical? - Jasmin Barman-Aksözen; Mattia Andreoletti; Alessandro Blasimme (Orphanet Journal of Rare Diseases, 2023)
Abstract A new active substance called “dersimelagon” (MT-7117) is being tested as an alternative treatment option for Erythropoietic protoporphyria (EPP). At the moment, dersimelagon is being tested both in the US and in Europe in a phase III placebo-controlled RCT. However, given the availability of an already approved treatment option for EPP the use of a placebo arm is questionable from an ethics point of view. We analyze the issue and suggest that a noninferiority active-control trial without placebo is an ethically and scientifically more valid design to test the efficacy of dersimelagon as well as other EPP treatments.